Il freudismo e la sinistra Considerazioni intorno a una vicenda editoriale - Maggiorelli, Simona (Il sogno della farfalla, 2006)
The article analyzes the case of a recent publication of the first two volumes of a new translation of Freud’s writings edited by Michele Ranchetti and the controversy which followed its immediate withdrawal. The author argues that the suppression of the new translation which succeeded in rendering Freud’s language closer to the original German and the criticisms that ensued from journalists and intellectuals aimed to hide the fact that Freudian thought is full of inconsistencies.